The complete chloroplast genome of an economic and ecological plant, paper mulberry (Broussonetia kazinoki × Broussonetia papyifera). Issue 1 (2nd January 2018) - Xu, Zhenggang; Yang, Guiyan; Dong, Meng; Wu, Liang; Zhang, Wan; Zhao, Yunlin
Abstract: The paper mulberry, Broussonetia kazinoki  ×  Broussonetia papyifera, is a species within the family Moraceae, also is an economic and ecological plant. Complete chloroplast genome of paper mulberry was reported in this study. The total genome size was 160, 903 bp in length, which is separated by a large single copy (LSC) region and a small single copy (SSC) region (89, 220 and 20, 079 bp in length, respectively). There were a total of 134 predicted functional genes, including 80 protein-coding genes (PCGs), eight ribosomal RNA (rRNA) genes, and 46 transfer RNA (tRNA) genes. The overall G + C content of the paper mulberry chloroplast genome was 35.74%, while the corresponding values of the LSC, SSC, and IR regions are 33.33%, 28.50%, and 42.72%, respectively. The phylogenetic analysis between Moraceae trees showed chloroplast genome of paper mulberry was closely related to Morus multicaulis .